Allograft Reconstruction of the Extensor Mechanism after Resection of Soft Tissue Sarcoma - Daniel A. Müller; Giovanni Beltrami; Guido Scoccianti; Pierluigi Cuomo; Francesca Totti; Rodolfo Capanna (Advances in Orthopedics)
Introduction. Soft tissue tumors around the knee joint still pose problems for the excision and subsequent reconstruction. Methods. In the 6 included patients the soft tissue sarcoma has its base on the anterior surface of the extensor mechanism and expands towards the skin. The entire extensor apparatus (quadriceps tendon, patella, and patellar tendon) was resected and replaced by a fresh-frozen allograft. Results. The mean follow-up was 6.7 years (range: 2–12.4 years). In two patients a local recurrence occurred, resulting in a 5-year local recurrence-free rate of 66.7% (95% CI: 19.5%–90.4%). Distant metastases were found in 4 patients resulting in a 5-year metastasis-free rate of 33.3% (95% CI: 4.6%–67.5%). Two patients underwent at least one revision surgery, including one patient in whom the allograft had to be removed. According to the ISOLS function score 24.7 points (range: 19–28 points) were achieved at the last follow-up. The mean active flexion of the knee joint was 82.5° (range: 25–120°) and a mean extension lag of 10° (range: 0–30°) was observed. Conclusions. The replacement of the extensor mechanism by an allograft is a reasonable option, allowing wide margins and restoration of active extension in most patients. Trial Registration. The presented study is listed on the ISRCTN registry with trial number ISRCTN63060594.